Meningkatkan Keterampilan Abad 21 di Sekolah Dasar: Rencana Aksi 2025 untuk Kritis, Kreatif, Kolaboratif - Oktaviani, Rina; Saputra, Dedi; Khairunnisa, Laila (FONDASI: Jurnal Pendidikan Dasar, 2026)
The 21st-century education transformation demands the development of critical, creative, collaborative, and communicative skills (4C) in elementary school students as a foundation for facing global challenges.  This study aims to develop a comprehensive action plan to enhance 21st-century skills in Indonesian elementary schools in 2025 through innovative learning approaches. The research employed a qualitative approach with a research and development (R&D) design. Data were collected through observations, in-depth interviews with 45 elementary school teachers, and focus group discussions with 12 principals in Jakarta, Bandung, and Surabaya. Data analysis utilized thematic analysis techniques. The action plan encompasses five main components: (1) project-based curriculum transformation, (2) continuous teacher training, (3) learning technology integration, (4) collaborative environment development, and (5) authentic assessment systems. Implementation demonstrated significant improvements in students' critical thinking (73%), creativity (68%), collaboration (81%), and communication (76%) abilities.  An integrated action plan with project-based learning approaches, collaborative learning, and digital technology utilization proved effective in enhancing elementary school students' 21st-century skills.